2021
DOI: 10.1016/j.cegh.2021.100705
|View full text |Cite
|
Sign up to set email alerts
|

“Factors influencing the outcome of COVID-19 patients admitted in a tertiary care hospital, Madurai.- a cross-sectional study”

Abstract: Introduction COVID19* is a new disease with significant mortality risk. Because of the scarcity of the study on factors associated with the mortality in Tamil Nadu present study was done to determine the factors associated with the outcome of the COVID19 patients admitted in a tertiary care hospital, Madurai. Method ology : 4530 lab confirmed COVID19 patients admitted from March to August 31st , 2020; excluding the non-responder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 18 publications
8
12
0
Order By: Relevance
“…The comorbidities in this study were cardiovascular disease, diabetes, and hypertension, respectively, agreeing with the findings of other studies [ 23 , 26 – 29 ]. Some studies reported that the prevalence of chronic kidney disease was higher among patients with GI symptoms [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The comorbidities in this study were cardiovascular disease, diabetes, and hypertension, respectively, agreeing with the findings of other studies [ 23 , 26 – 29 ]. Some studies reported that the prevalence of chronic kidney disease was higher among patients with GI symptoms [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…This might be one of the reasons for increased risk of mortality among the COVID-19 patients. The probability of survival was more than 80% if the patients got admitted within a week as compared to delayed admission, and this was in concordance with the findings by Priya S[ 7 ] who reported that it was more than 90% within 1 week and 80% between 7 and 10 days from the symptom onset to admission and gradually declined thereafter.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the majority of the deaths (53%) occurred in the older age group of more than 60 years, which was similar to findings by Priya S et al . [ 7 ] in which 59% of deaths occurred in the older age group and various studies[ 5 24 25 26 27 28 ] across the globe. Age-related factors such as declining immune functions, variations in quality and quantity of mucins and glycoproteins on the mucosal barriers and a gradual decline in clearing the inhaled particles could be attributed to increased risk of mortality among the elderly population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of subgroup analysis can be attributed to the predisposition of the disease in men, in which some studies reported that severe morbidity and mortality are more common in the male sex [22,23] . The more viral load and more severe disease may explain the higher AL, ACD and CCT measurements in men.…”
Section: Discussionmentioning
confidence: 99%